Principales factores de producción en el cultivo de pitahaya (Hylocereus spp.) en el Ecuador - López Santillán, Mariuxi Mayli (2023)
The objective of this document was to describe the main production factors in the cultivation of pitahaya (Hylocereus spp.) in Ecuador. For the elaboration of the document, information was obtained from updated texts, magazines, virtual libraries and scientific articles that contributed to the development of this document as a practical component of the degree work. The information obtained was paraphrased, summarized and analyzed allowing the development of the research. Production factors play an important role in the potential yield of the pitahaya crop, due to their direct interaction with the growth and vegetative development of the crop. The edaphoclimatic conditions that must be taken into consideration to establish a pitahaya plantation are the following: altitude, luminosity, precipitation, soil, temperature and humidity. The main agricultural management tasks for pitahaya cultivation include: propagation, soil preparation, layout, planting, planting, trellising, crop nutrition, irrigation, weed control, pruning, pest management and harvesting. The temperature required for pitahaya cultivation is 18 to 25 °C; temperature and luminosity are determining factors in production as they directly influence flowering and nutrient absorption. The pitahaya crop requires loamy, clayey, sandy soils with a high organic matter content, pH 5.3 to 7, and good drainage to avoid waterlogging. The growth of the pitahaya crop takes place in full sunlight, which is essential for the physiological process; under shade, yields are reduced according to the percentage of coverage; adequate lighting stimulates the emission of buds. For the good establishment of the crop, the soil should have adequate drainage to reduce production costs, otherwise it is necessary to build artificial drains to avoid phytosanitary problems due to excess moisture.